Penerapan Pendekatan Deep Learning Berbasis Smart TV dalam Meningkatkan Student Engagement pada Pembelajaran Matematika di SMP 4 Rejang Lebong - Siti Nabilah; Akbar Effendi; Syaripah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
Conventional methods that remain dominant in mathematics instruction tend to render students passive, prone to boredom, and challenged by abstract concepts. This study aims to describe the implementation of a Smart TV-based